Proceedings of the 50th Annual Design Automation Conference 2013
DOI: 10.1145/2463209.2488830
|View full text |Cite
|
Sign up to set email alerts
|

Role of power grid in side channel attack and power-grid-aware secure design

Abstract: Side-channel attack (SCA) is a method in which an attacker aims at extracting secret information from crypto chips by analyzing physical parameters (e.g. power). SCA has emerged as a serious threat to many mathematically unbreakable cryptography systems. From an attacker's point of view, the difficulty of mounting SCA largely depends on Signal-to-Noise Ratio (SNR) of the side-channel information. It has been shown that SNR primarily depends on algorithmic and circuit-level implementation, measurement noise, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Wang et al studied the design of power grids to deter power attacks [Wan13]. They showed that the current pattern generated by a circuit is filtered by the PDN before it can be observed at the pins making the 'logical' and 'physical' current patterns different.…”
Section: Previous Workmentioning
confidence: 99%
“…Wang et al studied the design of power grids to deter power attacks [Wan13]. They showed that the current pattern generated by a circuit is filtered by the PDN before it can be observed at the pins making the 'logical' and 'physical' current patterns different.…”
Section: Previous Workmentioning
confidence: 99%
“…In particular, power dissipation and electromagnetic (EM) emissions from modern SoCs can leak compromising information and has emerged as key threats to security of modern SoCs. Consequently, power and EM side channel attack on AES architectures have received signifcant attention over last decade [2], [7]- [11]. Although majority of the works focus on inhibiting power attacks, preventing EM attacks is gaining more importance in the era of mobile and ubiquituous computing, due to the simplicity and inexpensive nature of the EM attack.…”
Section: Introductionmentioning
confidence: 99%
“…Placement performance largely impacts the downstream stages of power grid design [Wang et al 2013], clock tree synthesis [Lu et al 2012a], power optimization [Lu et al 2012b], global detail routing [Lu and Sham 2013], postlayout simulation [He et al 2012], and design variability [Zheng et al 2014]. As the technology node enters the deep nanometer scale [ITRS 2011] with billion-transistor integration, the performance of the placement engine becomes dominant on the overall quality of the design.…”
Section: Introductionmentioning
confidence: 99%